Endometrial local injury, a simple procedure that improves IVF outcome in a selected population of patients - Irit Granot; Nava Dekel (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
Embryo implantation, an essential prelude for the establishment of pregnancy, is successful upon the interaction of a high-quality embryo with a receptive uterus. Nevertheless, 'inadequate uterine receptivity' which has been pointed out as the cause for approximately two-thirds of repeated implantation failures (RIF, [1-3]), combined with the low rate of implantation (~25%) obtained upon transfer of good embryos in IVF, makes implantation the rate-limiting step for the success of ART.